Reclaiming sacred knowledge: Afghan women’s agency and Islamic education in post-2021 Afghanistan - Basira Mujadidi; Fayza Mujadidi (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2025)
Islamic education is a fundamental right in Islamic tradition for both women and men. However, in Afghanistan, women’s access to Islamic education has fluctuated across political regimes and has been severely restricted since the Taliban’s return to power in 2021. These restrictions have intensified debates about the relationship between Islamic doctrine, political authority, and women’s religious agency. This study aims to examine the evolution of women’s Islamic education in Afghanistan, identify contemporary opportunities and barriers to access, and explore how women contribute to transforming Islamic educational thought and practice in the post-2021 context. Using a qualitative exploratory design, the study draws on semi-structured interviews with seven women involved in Islamic education, as students, teachers, and religious educators, across Kabul, Herat, and Nangarhar, complemented by document analysis of policy reports, academic literature, and media sources. Data were analyzed thematically. The findings show that women’s Islamic education is shaped primarily by political regimes rather than Islamic doctrine. While formal access has declined sharply since 2021, women continue to engage in Islamic learning through informal, community-based, and limited digital initiatives. Women also play an active role in reshaping pedagogy and interpretation, emphasizing understanding, ethical reflection, and relevance to lived experience. The study highlights women’s agency and grassroots educational resilience, underscoring the need for offline-first, community-centered Islamic education strategies and greater support for female religious educators in Afghanistan.